Porous carbon positive electrode material with high sulfur loading capacity and application of porous carbon positive electrode material
By using porous carbon materials made from lithium hydride and lithium carbonate as sulfur carriers in lithium sulfur batteries and building a conductive network, the problem of insufficient performance of lithium sulfur batteries under high sulfur proportion is solved, and the effects of high discharge capacity, long cycle life and high energy density are achieved.
Patent Information
- Application Number
- CN202411959469.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-11
AI Technical Summary
With the high sulfur proportion, existing lithium-sulfur batteries lack performance such as discharge capacity, cycle life and energy density, making it difficult to achieve high-quality energy density and volume energy density.
The porous carbon material produced by heating reaction of lithium hydride and lithium carbonate is used as the carrier of sulfur, and a positive electrode conductive network is constructed through conductive agents to improve the rate performance and cycle life of the battery.
The application of porous carbon positive electrode material with a high sulfur proportion in lithium-sulfur batteries has been achieved, and the discharge specific capacity, cycle stability and energy density of the battery have been improved, and excellent electrochemical performance has been shown.
Smart Images

Figure CN119812260A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium-sulfur batteries, and in particular to a porous carbon material with a high sulfur loading and application thereof. Background Art
[0002] As the main energy source for people today, fossil energy is widely used in various fields. However, with the extensive use of traditional fossil energy, some problems have emerged, such as low utilization rate of fossil energy combustion and large exhaust pollution after combustion. Traditional fossil energy can no longer meet the requirements of low-carbon environmental protection and sustainable development. Therefore, new energy has emerged in this era. Due to the large-scale use of electric technology products such as electronic products and electric vehicles, people have put forward higher requirements on the energy density of batteries, the power source of these electric products. Lithium-sulfur batteries with outstanding advantages in energy density have attracted the attention of researchers. Sulfur has the advantages of high theoretical specific capacity (1675mAh / g), as well as its abundant reserves, low price and environmental friendliness, making it a potential next-generation lithium battery positive electrode material.
[0003] At present, the application of lithium-sulfur batteries is seriously affected by insulating sulfur, large volume changes (lithiation / stripping rate up to 80%) and the shuttling effect of lithium polysulfide. The low conductivity of sulfur and intermediates and the polysulfide (PS) products formed during the cycle increase the resistance of the battery and affect the battery performance. In addition, it will also lead to unstable electrochemical contact in the positive electrode. Large volume changes in the electrode will cause the electrode to crush and lead to capacity decay. In order to inhibit or alleviate the shuttling of polysulfides and improve the conductivity of the electrode, porous carbon is introduced into the positive electrode system as a sulfur skeleton. Porous carbon materials have good compatibility with carbonate-based electrolytes, and they are stable, non-toxic and easy to infiltrate. At the same time, due to different porosities and structures, porous carbon-based materials have multiple advantages as sulfur carriers. On the one hand, porous carbon materials can be used as conductive agents to improve the conductivity of the electrode. On the other hand, porous carbon has a high specific surface area, which can physically confine polysulfides and effectively alleviate the shuttle effect.
[0004] Lithium-sulfur batteries have a theoretical energy density of up to 2600 Wh / kg, but in current reports, the mass energy density of lithium-sulfur batteries is much lower than the theoretical energy density. In order to maximize the advantages of lithium-sulfur batteries, it is necessary to significantly increase their mass energy density and volume energy density. For example, a Chinese patent with authorization announcement number CN111180681A discloses a method for preparing multi-level porous graphitized carbon and its application in sulfur-carbon positive electrodes. It reports the electrochemical lithium storage performance of sulfur-carbon positive electrodes with a sulfur ratio (including carbon materials, conductive agents and binders, etc., the same sulfur ratio is expressed below) of 60wt.%, and a charge and discharge cycle life of less than 100 times. Noel Díez et al. reported a tannic acid-derived porous carbon / sulfur composite material (Noel Díez, Guillermo A. Ferrero, Marta Sevilla, et al. “A simple and general approachfor in situ synthesis of sulfur–porous carbon composites for lithium–sulfurbatteries” Sustainable Energy Fuels, 2019, 3, 3498–3509). The highest sulfur content reported was 68.88 wt.%, and the discharge specific capacity was only ~800 mAh / g (about 50% of the theoretical value). Existing studies have shown that the specific capacity, cycle life and other properties of sulfur-carbon cathodes will deteriorate with increasing sulfur content. Simultaneously achieving a high sulfur content and a high specific capacity of active sulfur is the most effective way to increase battery energy density. Therefore, how to simultaneously achieve a high sulfur content and a high specific capacity of active sulfur, thereby improving battery energy density, cycle life and other performance, is an urgent problem to be solved. Summary of the invention
[0005] In view of the shortcomings of the prior art, the first object of the present invention is to provide a porous carbon positive electrode material with a high sulfur loading, which has a high discharge capacity, excellent rate performance and cycle stability under the premise of a high sulfur ratio.
[0006] The second object of the present invention is to provide an application of a porous carbon positive electrode material with a high sulfur loading, which achieves an ultra-high sulfur ratio and is beneficial to improving the mass energy density and volume energy density of lithium-sulfur batteries.
[0007] To achieve the above first object, the present invention provides the following technical solutions: A porous carbon positive electrode material with a high sulfur loading is made of raw materials containing the following weight percentages: 70.0-90.0% sulfur, 5.0-15.0% porous carbon, 4.0-10.0% conductive agent, and 1.0-4.0% binder; wherein the porous carbon is made by heating lithium hydride and lithium carbonate.
[0008] Furthermore, the porous carbon positive electrode material with a high sulfur loading is made of raw materials containing the following weight percentages: 80% sulfur, 10.0% porous carbon, 7.5% conductive agent, and 2.5% binder.
[0009] Furthermore, the porous carbon material is prepared by heating 0.5-2.0 parts of lithium hydride and 1.0-5.0 parts of lithium carbonate.
[0010] Furthermore, the average particle size of lithium hydride is controlled to be 5-20 μm and 200-400 μm, and the average particle size of lithium carbonate is controlled to be 30-90 μm; no grinding balls are added during the ball milling process, the ball milling speed is 200-300 rpm, and the ball milling time is 1.5-2.5 h.
[0011] Furthermore, the preparation process of the porous carbon cathode material with high sulfur loading includes: S1: First, lithium hydride and lithium carbonate are mixed in a mass ratio of 0.5-2.0:1.0-5.0, ball-milled in an argon atmosphere, and then heated to 200-250°C at 0.1-10.0°C / min to start the reaction, and then heated to 480-520°C at 0.1-2.0°C / min, and the reaction is continued for 1-5 hours. After the reaction is completed, the porous carbon material is obtained by post-treatment; S2 first mixes sulfur, porous carbon material, conductive agent and binder, grinds them in a mixer, and then performs vacuum heat treatment at 110~160℃ for 0.5~1.5h to obtain a porous carbon positive electrode material with high sulfur loading.
[0012] Furthermore, in S1, the particle size of lithium hydride is controlled to be in the range of 5-20 μm and 200-400 μm, and the particle size of lithium carbonate is controlled to be in the range of 30-90 μm; Furthermore, in S1, no ball milling beads are added during the ball milling process, the ball milling speed is 200-300 rpm, and the ball milling time is 1.5-2.5 h.
[0013] Furthermore, in S1, after the reaction is completed, the reactant is acid-washed with dilute hydrochloric acid for 2-30 hours, filtered, and the obtained filter residue is dried at 60-150° C. for 10-15 hours to obtain a porous carbon material. The dilute hydrochloric acid is prepared by dissolving 36-38 wt.% concentrated hydrochloric acid in deionized water at a volume ratio of 1:3.
[0014] Furthermore, in S1, the porous carbon includes a plurality of micropores with a pore size of 1.14±0.10 nm, a plurality of mesopores with a pore size range of 2.00-50.00 nm, and a plurality of macropores with a pore size range of 50.00-60.00 nm and above 100.00 nm, and the average pore size of the porous carbon is 2-20 nm, and the total pore volume is 0.1-5.0 cm 3 / g, BET specific surface area is 700~1200m 2 / g.
[0015] Furthermore, the conductive agent is one or a combination of conductive carbon black (Super P), carbon nanotubes (SWCNT) and acetylene black (ACET).
[0016] Furthermore, the binder is one of sodium carboxymethyl cellulose (CMC), acrylonitrile multipolymer (LA133 water-based binder) and polyvinylidene fluoride (PVDF).
[0017] To achieve the above second purpose, the present invention provides the following technical solutions: Application of a porous carbon cathode material with high sulfur loading in lithium-sulfur batteries.
[0018] Furthermore, the porous carbon cathode material with high sulfur loading is first mixed with a dispersion medium, and the sulfur loading is 0.5-5.0 mg / cm 2 The positive electrode is coated on the surface of the aluminum current collector, and after coating, it is post-processed to obtain a positive electrode plate; the positive electrode plate is used as a working electrode, lithium metal is used as a counter electrode, and a diaphragm and an electrolyte are set to assemble a lithium-sulfur battery.
[0019] Furthermore, the mass ratio of the sulfur-carbon cathode material to the dispersion medium is 1:5-20.
[0020] Furthermore, the dispersion medium is N-methylpyrrolidone (NMP) or water.
[0021] Furthermore, the post-treatment method is drying at 60-100° C. for 10-15 hours.
[0022] Furthermore, the separator is a polypropylene film (PP) and / or a polyethylene film (PE).
[0023] Furthermore, the electrolyte in the electrolyte is lithium bis(trifluoromethylsulfonyl)imide (LiTFSI).
[0024] Furthermore, the solvent in the electrolyte is ethylene glycol dimethyl ether (DME) and 1,3-dioxolane (DOL).
[0025] Furthermore, the electrolyte also includes lithium nitrate.
[0026] Furthermore, the electrolyte concentration of the electrolyte is 0.8-1.2 mol / L, and the lithium nitrate concentration is 1.8-2.2 wt.%.
[0027] In summary, the beneficial technical effects of the present invention are: 1. The present invention uses lithium hydride and lithium carbonate to react by heating to prepare a porous carbon material having a sponge-like hierarchical porous structure and a large specific surface area. The porous carbon material has a low crystallinity, a large peak width in the X-ray diffraction spectrum, and a relatively sharp peak. The pores are evenly distributed and have a connected pore structure. The porous carbon material is used as a sulfur-carrying body, and a conductive agent is used to construct a good positive electrode conductive network between the sulfur-carrying bodies, which can effectively improve the rate performance and cycle life of the battery. 2. In the porous carbon cathode material with high sulfur loading of the present invention, the macropores in the porous carbon material provide space for accommodating sulfur, which can fully cope with the volume expansion of sulfur during the charge and discharge process. The micropores can effectively inhibit the shuttle effect of lithium polysulfide. The rich porous structure is interconnected to form a conductive network, which ensures the good conductivity of the cathode material, so that the lithium-sulfur battery has high discharge specific capacity, long cycle life, high mass energy density and volume energy density, excellent electrochemical performance and high practical value. At the same time, the sulfur / porous carbon cathode material has excellent performance, simple and green preparation process, suitable for commercialization, and has broad market application prospects; 3. After the porous carbon cathode material with high sulfur loading of the present invention is applied to the lithium-sulfur battery, the first discharge capacity of the lithium-sulfur battery at 0.05C is 1337mAh / g, and the first efficiency is 97.43%; at a current density of 0.5C, the discharge capacity is 905mAh / g; at the same time, it has excellent cycle performance, and the capacity retention rate after 300 cycles is 85.47%, and the average attenuation rate each time is 0.048%; 4. The lithium-sulfur battery of the present invention has significantly better electrochemical performance than existing lithium-sulfur batteries, breaking through the current thinking limitations in the field, and providing a new research and development direction and application idea for the field of lithium-sulfur batteries and the selection of positive electrode sulfur carrier materials, which is of great significance. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is the XRD diagram of the porous carbon material of Example 1 of the present invention.
[0029] Figure 2 This is a SEM image of the porous carbon material of Example 1 of the present invention.
[0030] Figure 3 This is a pore size distribution diagram of the porous carbon material of Example 1 of the present invention.
[0031] Figure 43 is a nitrogen adsorption-desorption curve diagram of the porous carbon material of Example 1 of the present invention.
[0032] Figure 5 This is a SEM image of the porous carbon material with high sulfur loading according to Example 1 of the present invention.
[0033] Figure 6 This is a constant current charge and discharge curve diagram of the porous carbon material with high sulfur loading in Example 1 of the present invention.
[0034] Figure 7 This is a cycle performance diagram of the lithium-sulfur battery of Example 1 of the present invention.
[0035] Figure 8 This is a rate performance diagram of the lithium-sulfur battery of Example 1 of the present invention.
[0036] Fig. 9 It is a cycle performance diagram of the lithium-sulfur battery of Comparative Example 1 of the present invention.
[0037] Fig.10 It is a cycle performance diagram of the lithium-sulfur battery of Comparative Example 2 of the present invention.
[0038] Fig.11 It is a cycle performance diagram of the lithium-sulfur battery of Comparative Example 3 of the present invention.
[0039] Fig.12 It is a cycle performance diagram of the lithium-sulfur battery of Comparative Example 4 of the present invention. DETAILED DESCRIPTION
[0040] In order to make the technical means, creative features, objectives and functions achieved by the present invention clearer and easier to understand, the present invention is further explained below in conjunction with the accompanying drawings and specific implementation methods. Example
[0041] Example 1: A porous carbon cathode material with high sulfur loading disclosed in the present invention, which is specifically implemented as follows: S1: First, 1.2 g of lithium hydride and 2.8 g of lithium carbonate were mixed in a glove box, and the mixture was placed in a ball milling jar. In an argon atmosphere, the mixture was ball milled on a planetary ball mill. No ball milling beads were added during the ball milling process. The ball milling speed was 200 rpm and the ball milling time was 2.0 h. Then, the ball-milled sample was taken out of the glove box and placed in a reactor. This reactor can detect the temperature and air pressure in the tube. The temperature was raised to 230 °C at 5.0 °C / min to start the reaction, and then the temperature was raised to 500 °C at 0.5 °C / min. The reaction was continued for 1 h. After the reaction was completed, the reactant was acid-washed with dilute hydrochloric acid for 24 h, filtered, and the obtained filter residue was dried at 80 °C for 12 h to obtain a porous carbon material. S2 prepares raw materials according to the following weight percentages, including 80.0% sulfur (S), 10.0% porous carbon (HPC) prepared from S1, 7.5% conductive agent (SWCNT) and 2.5% binder (PVDF), and mixes the raw materials, grinds them in a mixer, and then heats them at 155°C in vacuum for 1.0h to obtain a porous carbon positive electrode material with a high sulfur loading.
[0042] Figure 1 is the XRD diagram of the porous carbon material of this embodiment, Figure 1 It can be seen that the main peak is wider and more blunt, which indicates that its crystallinity is lower.
[0043] Figure 2 (a)-(b) are SEM images of the porous carbon material of this embodiment. Figure 2 (a) It can be seen that the surface is flat and smooth and no obvious pore structure can be seen. The porous carbon surface is composed of abundant micropores and mesopores. Figure 2 (b) It can be seen that at the fracture of the porous carbon, it can be clearly seen that there are abundant macropores inside and they are evenly distributed; from the two figures, it can be seen that the porous carbon material presents a hierarchical porous structure in which macropores, mesopores and micropores coexist and are interconnected, and the porous carbon as a whole appears sponge-like.
[0044] Figure 3 is a nitrogen adsorption-desorption curve of the porous carbon material of this embodiment, from Figure 3 It can be seen that the nitrogen adsorption-desorption curve of the porous carbon material presents a mixed curve of type I and type IV, indicating that its pore structure is composed of micropores, mesopores and macropores.
[0045] Figure 4 This is the pore size distribution diagram of the porous carbon material prepared in this embodiment. It can be seen from the figure that the porous carbon material has macropores, mesopores and micropores at the same time. The micropore diameter is concentrated at 1.14±0.10nm; the mesopores are continuously distributed in the pore size range of 2~50 nm; the macropores are distributed in the range of 50~60 nm, 100nm and larger. The present invention also discloses an application of a porous carbon positive electrode material with a high sulfur loading in a lithium-sulfur battery, and its specific implementation method is as follows: S1 mixes sulfur / porous carbon cathode material and dispersion medium (NMP), the mass ratio of cathode material to dispersion medium is 1:5~20, and the sulfur loading is 0.5~5.0mg / cm 2 Coated on the surface of aluminum current collector (carbon-coated aluminum foil), and dried at 60°C for 12h after coating to obtain a positive electrode sheet; S2 uses the positive electrode as the working electrode, lithium metal as the counter electrode, and is provided with a diaphragm (PP, Celgard2500) and an electrolyte (1M LiTFSI in DME: DOL=1:1 Vol% with 2 wt.% LiNO3). A CR2032 button battery shell is used in a glove box filled with argon gas. The battery is assembled in the order of positive electrode shell, positive electrode sheet, diaphragm, and lithium metal negative electrode from bottom to top. An appropriate amount of the above electrolyte is added, the negative electrode shell is covered, and finally sealed with a sealing machine to obtain a lithium-sulfur battery.
[0046] Figure 5 This is a SEM image of a high sulfur content positive electrode conductive network constructed using the prepared porous carbon material as the sulfur carrier main material in this embodiment. Figure 5 It can be seen that the macropores in the porous carbon material provide space to accommodate sulfur, which can fully cope with the volume expansion of sulfur during the charging and discharging process; at the same time, the micropores on the surface of the porous carbon material can effectively inhibit the shuttle effect of lithium polysulfide; the rich porous structure and single-walled carbon nanotubes are interconnected to form a conductive network, ensuring the good conductivity of the composite material.
[0047] The assembled lithium-sulfur battery was activated three times at 0.05C and once at 0.5C, and then charged and discharged at 0.25C-0.5C for cycle performance testing.
[0048] Figure 6 The figure shows the charge and discharge curve of the lithium-sulfur battery assembled with the porous carbon material prepared in this embodiment as the sulfur carrier main material. Figure 6 As shown, the first discharge capacity at 0.05C is 1337mAh / g, the first coulombic efficiency is 97.43%, and the charge and discharge curves corresponding to the second and third cycles are almost identical, showing excellent reversibility.
[0049] Figure 7 The figure shows the cycle performance of the lithium-sulfur battery assembled with the porous carbon material prepared in this embodiment as the sulfur carrier main material. As shown in the figure, at a current density of 0.5C, the discharge capacity is 905mAh / g; at the same time, it has excellent cycle performance. After 300 cycles, the capacity retention rate is 85.47%, and the average attenuation rate each time is 0.048%, which has excellent cycle performance.
[0050] The assembled lithium-sulfur battery was charged and discharged 10 times at 0.1C, 0.2C, 0.5C, 1C, and 2C, and its rate performance was tested.
[0051] Figure 8The figure shows the rate performance of the lithium-sulfur battery assembled with the porous carbon material prepared in this embodiment as the sulfur carrier main material. The corresponding reversible capacities at current densities of 0.1C, 0.2C, 0.5C, 1C, and 2C are 1137, 1014, 853, 720, and 601 mAh / g, respectively, showing excellent rate performance.
[0052] Example 2: This is a porous carbon positive electrode material with a high sulfur loading disclosed in the present invention. The difference from Example 1 is that in S1, the temperature is raised to 230°C at 5.0°C / min to start the reaction, then the temperature is raised to 500°C at 2.0°C / min, and the reaction is continued at this temperature for 1 hour.
[0053] The present invention also discloses an application of a porous carbon positive electrode material with a high sulfur loading in a lithium-sulfur battery, and its specific implementation method is the same as that of Example 1.
[0054] Example 3: This is a porous carbon positive electrode material with a high sulfur loading disclosed in the present invention. The difference from Example 1 is that in S1, the temperature is raised to 230°C at 5.0°C / min to start the reaction, then the temperature is raised to 500°C at 5.0°C / min, and the reaction is continued at this temperature for 1 hour.
[0055] The present invention also discloses an application of a porous carbon positive electrode material with a high sulfur loading in a lithium-sulfur battery, and its specific implementation method is the same as that of Example 1.
[0056] Embodiment 4 is a porous carbon cathode material with high sulfur loading disclosed in the present invention. The difference from Embodiment 1 is that the specific implementation method is as follows: S1: First, 0.5g lithium hydride and 1.0g lithium carbonate were mixed in a glove box, and the mixture was placed in a ball milling jar. In an argon atmosphere, the mixture was ball milled on a planetary ball mill. No ball milling beads were added during the ball milling process. The ball milling speed was 400rpm and the ball milling time was 1.5h. Then, the ball-milled sample was taken out of the glove box and placed in a reactor. This reactor can detect the temperature and air pressure in the tube. The temperature was raised to 200℃ at 2℃ / min to start the reaction, and then the temperature was raised to 480℃ at 0.1℃ / min. The reaction was continued for 1h. After the reaction was completed, the reactant was acid-washed with dilute hydrochloric acid for 24h, filtered, and the obtained filter residue was dried at 80℃ for 12h to obtain a porous carbon material. S2 prepares raw materials according to the following weight percentages, including 70.0% sulfur (S), 15.0% porous carbon (HPC) prepared from S1, 10.0% conductive agent (Super P) and 5.0% binder (CMC), and mixes the raw materials, grinds them in a mixer, and then heats them at 110°C in vacuum for 0.5h to obtain a porous carbon positive electrode material with a high sulfur loading.
[0057] Example 5: A porous carbon cathode material with a high sulfur loading disclosed in the present invention, which is different from Example 1 in that its specific implementation method is: S1: First, 2.0 g of lithium hydride and 5.0 g of lithium carbonate were mixed in a glove box, and the mixture was placed in a ball milling jar. In an argon atmosphere, the mixture was ball milled on a planetary ball mill. No ball milling beads were added during the ball milling process. The ball milling speed was 600 rpm and the ball milling time was 2.5 h. Then, the ball-milled sample was taken out of the glove box and placed in a reactor. This reactor can detect the temperature and air pressure in the tube. The temperature was raised to 250 °C at 10.0 °C / min to start the reaction, and then the temperature was raised to 520 °C at 2.0 °C / min. The reaction was continued for 5 h. After the reaction was completed, the reactant was acid-washed with dilute hydrochloric acid for 24 h, filtered, and the obtained filter residue was dried at 80 °C for 12 h to obtain a porous carbon material. S2 prepares raw materials according to the following weight percentages, including 90.0% sulfur (S), 5.0% porous carbon (HPC) prepared from S1, 4.0% conductive agent (ACET) and 1.0% binder (LA133 aqueous binder), and mixes the raw materials, grinds them in a mixer, and then heats them at 160°C in vacuum for 1.5h to obtain a porous carbon positive electrode material with a high sulfur loading.
[0058] Example 6: Application of a porous carbon material with high sulfur loading in a lithium-sulfur battery disclosed in the present invention, which is different from Example 1 in that its specific implementation method is: S1 mixed the sulfur / porous carbon cathode material and the dispersion medium (N-methylpyrrolidone) in a mass ratio of 1:5, and the sulfur loading was 0.5 mg / cm 2 Coated on the surface of aluminum current collector (carbon-coated aluminum foil), and dried at 60°C for 12h after coating to obtain a positive electrode sheet; S2 uses the positive electrode as the working electrode, lithium metal as the counter electrode, and is provided with a diaphragm (PP, Celgard2500) and an electrolyte (1M LiTFSI in DME: DOL=1:1 Vol% with 2wt.% LiNO3). A CR2032 button battery shell is used in a glove box filled with argon gas. The shell, positive electrode sheet, diaphragm, and lithium metal negative electrode are assembled in the order from bottom to top. An appropriate amount of the above electrolyte is added, the negative electrode shell is covered, and finally sealed with a sealing machine to obtain a lithium-sulfur battery.
[0059] Example 7: Application of a porous carbon cathode material with a high sulfur loading in a lithium-sulfur battery disclosed in the present invention, which is different from Example 5 in that its specific implementation method is: S1: Mix the sulfur / porous carbon cathode material and the dispersion medium (water) in a mass ratio of 1:20, and add a sulfur loading of 5.0 mg / cm2 Coated on the surface of aluminum current collector (carbon-coated aluminum foil), and dried at 60°C for 12h after coating to obtain a positive electrode sheet; S2 uses the positive electrode as the working electrode, lithium metal as the counter electrode, and is provided with a diaphragm (PE) and an electrolyte (1MLiTFSI in DME: DOL=1:1 Vol% with 2wt.% LiNO3). A CR2032 button-type battery shell is used in a glove box filled with argon gas. The battery is assembled in the order of positive electrode shell, positive electrode sheet, diaphragm, and lithium metal negative electrode from bottom to top. An appropriate amount of the above electrolyte is added, the negative electrode shell is covered, and finally sealed with a sealing machine to obtain a lithium-sulfur battery.
[0060] Comparative Example 1: This is the application of a porous carbon positive electrode material with a high sulfur loading in a lithium-sulfur battery disclosed in the present invention. The difference from Example 1 is that the basswood is soaked in a mixture of a sodium hydroxide solution and a sodium sulfite solution, and soaked at 80°C for 12 hours to remove the lignin in the basswood. It is then washed with deionized water until neutral and dried, and the dried basswood is soaked again in a 30% hydrogen peroxide solution to further remove the lignin. Subsequently, the basswood is washed in deionized water until neutral and dried. The dried basswood is placed in a tubular furnace, heated to 260°C at 5.0°C min in an argon atmosphere for 3 hours, and then heated to 1000°C at 5.0°C / min and kept warm for 6 hours. The heated product is soaked in a potassium hydroxide solution, soaked at 90°C for 1 hour, washed with hydrochloric acid and dried to obtain a porous carbon material.
[0061] Comparative Example 2: The application of a porous carbon positive electrode material with a high sulfur loading in a lithium-sulfur battery disclosed in the present invention is different from Example 1 in that the poplar wood is soaked in a mixture of a sodium hydroxide solution and a sodium sulfite solution, and soaked at 80°C for 12 hours to remove the lignin in the poplar wood. Subsequently, it is washed with deionized water until neutral and dried, and the dried poplar wood is soaked again in a 30% hydrogen peroxide solution to further remove the lignin. Subsequently, the poplar wood is washed in deionized water until neutral and dried. The dried poplar wood is placed in a tubular furnace, heated to 260°C at 5.0°C / min in an argon atmosphere for 3 hours, and then heated to 1000°C at 5.0°C / min and kept warm for 6 hours. The heated product is soaked in a potassium hydroxide solution, soaked at 90°C for 1 hour, washed with hydrochloric acid, and dried to obtain a porous carbon material.
[0062] Comparative Example 3: Application of a porous carbon cathode material with high sulfur loading in a lithium-sulfur battery disclosed in the present invention. The difference from Example 1 is that bamboo is washed and crushed, and the bamboo scraps are placed in a tubular furnace, and the temperature is raised to 600 °C at 5.0 °C / min in an argon atmosphere for 6 h. After cooling to room temperature, it is boiled with hydrochloric acid, then washed with deionized water until neutral, and dried to obtain a porous carbon material.
[0063] Comparative Example 4: Application of a porous carbon cathode material with a high sulfur loading disclosed in the present invention in a lithium-sulfur battery. The difference from Example 1 is that commercially available capacitor carbon is used instead of the porous carbon material.
[0064] First, the specific surface area, average pore diameter and total pore volume of the porous carbon materials prepared in Examples 1 to 3 and Comparative Examples 1 to 4 were tested. The results are shown in Table 1.
[0065] Table 1 <![CDATA[Specific surface area (m 2 / g)]]> Average pore size (nm) <![CDATA[Total pore volume (cm 3 / g)]]> Example 1 1079 13.12 2.38 Example 2 928 12.77 1.78 Example 3 783 12.56 1.58 Comparative Example 1 492 2.82 0.35 Comparative Example 2 834 2.32 0.483 Comparative Example 3 585 2.89 0.206 Comparative Example 4 2000 2.97 0.294 Then, activation was performed three times at a current density of 0.05C, and activation was performed again at a current density of 0.5C. After that, charge and discharge were performed at a current density of 0.25C~0.5C, and the cycle performance test was performed. The results are shown in Table 2.
[0066] Table 2 shows the first discharge capacity and first coulombic efficiency of lithium-sulfur batteries prepared from porous carbon materials of Examples 1 to 3 and Comparative Examples 1 to 4 at a current density of 0.05C.
[0067] Table 2 First discharge capacity (mAh / g) First coulombic efficiency (%) Example 1 1337 97.43 Example 2 1290 95.21 Example 3 1211 94.49 Comparative Example 1 820 86.55 Comparative Example 2 901 92.59 Comparative Example 3 1095 90.11 Comparative Example 4 1038 91.53 It can be seen from Table 2 that the porous carbon materials prepared in Examples 1 to 3 are used as sulfur carriers for the positive electrode of lithium-sulfur batteries. The first discharge capacity of the assembled lithium-sulfur batteries at a current density of 0.05C is higher than 1200mAh / g, and the first coulombic efficiency is more than 95%, which is higher than the performance of general porous carbon materials in the first discharge of lithium-sulfur batteries and has good electrochemical properties.
[0068] The capacity retention rate and coulombic efficiency of the lithium-sulfur batteries assembled with the porous carbon materials prepared in Examples 1 to 3 and Comparative Examples 1 to 4 after 300 charge and discharge cycles at a current density of 0.25C to 0.5C are shown in Table 3. Figures 7 to 12 shown.
[0069] Table 3 0.5C discharge capacity (mAh / g) Capacity retention rate (%) Coulomb efficiency (%) Example 1 905 85.49 98.21 Example 2 885 82.54 96.78 Example 3 850 80.36 95.65 Comparative Example 1 431 72.92 88.17 Comparative Example 2 503 75.94 94.91 Comparative Example 3 661 90.67 94.15 Comparative Example 4 631 87.38 94.57 It can be seen from Table 3 that the porous carbon materials prepared by Examples 1 to 3 are used as sulfur carriers for the positive electrode of lithium-sulfur batteries, and the assembled lithium-sulfur batteries can reach a capacity of 850mAh / g at a current density of 0.5C. Compared with the implementation case, the comparative case can only maintain a lower discharge capacity at a current density of 0.5C; Examples 1 to 3 have a capacity retention rate of not less than 80% after 300 cycles at a current density of 0.25C to 0.5C, and can still maintain ultra-high coulombic efficiency after 300 cycles. Among them, in Implementation Case 1, the capacity retention rate is as high as 85.49% after 300 cycles, and the average attenuation rate is 0.048% each time. It not only performs well in lithium-sulfur batteries, but also performs very well in conventional lithium-sulfur batteries. It can still maintain a coulombic efficiency of 98.21% after 300 cycles, effectively suppressing the shuttle effect during the cycle. It is significantly higher than that of comparative examples 1 to 4; the sponge-like hierarchical porous carbon material of the present invention has a large specific surface area and rich pore size, and the macropores in the porous carbon provide space for accommodating sulfur, which can fully cope with the volume expansion of sulfur during the charge and discharge process; at the same time, the micropores on the surface of the sponge-like hierarchical porous carbon can effectively inhibit the shuttle effect of lithium polysulfide; the rich porous structure is interconnected to form a conductive network, which ensures the good conductivity of the composite material. In turn, the lithium-sulfur battery exhibits high discharge capacity, high cycle stability, and high coulombic efficiency.
[0070] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.
Claims
1. A porous carbon cathode material with high sulfur loading, characterized in that: The porous carbon is prepared from raw materials containing the following weight percentages: 70.0-90.0% sulfur, 5.0-15.0% porous carbon, 4.0-10.0% conductive agent, and 1.0-4.0% binder; wherein the porous carbon is prepared by heating lithium hydride and lithium carbonate.
2. The porous carbon cathode material with high sulfur loading according to claim 1, characterized in that: The porous carbon material is prepared by heating 0.5-2.0 parts of lithium hydride and 1.0-5.0 parts of lithium carbonate.
3. The porous carbon cathode material with high sulfur loading according to claim 2, characterized in that: The preparation process of the porous carbon positive electrode material with high sulfur loading includes: S1: First, lithium hydride and lithium carbonate are mixed in a mass ratio of 0.5-2.0:1.0-5.0, ball-milled in an argon atmosphere, and then heated to 200-250°C at 0.1-10.0°C / min to start the reaction, and then heated to 480-520°C at 0.1-2.0°C / min, and the reaction is continued for 1-5 hours. After the reaction is completed, the porous carbon material is obtained by post-treatment; S2 first mixes sulfur, porous carbon material, conductive agent and binder, grinds them in a mixer, and then heats them in a vacuum at 110-160°C for 0.5-1.5h to obtain a porous carbon positive electrode material with a high sulfur loading.
4. The porous carbon material with high sulfur loading according to claim 3, characterized in that: In S1, the particle size range of lithium hydride is controlled to be 5-20 μm and 200-400 μm, and the particle size range of lithium carbonate is controlled to be 30-90 μm; no grinding balls are added during the ball milling process, the ball milling speed is 200-300 rpm, and the ball milling time is 1.5-2.5 h.
5. The porous carbon cathode material with high sulfur loading according to claim 3, characterized in that: In S1, after the reaction is completed, the reactant is acid-washed with dilute hydrochloric acid for 2-30 hours, filtered, and the obtained filter residue is dried at 60-150° C. for 10-15 hours to obtain a porous carbon material. The dilute hydrochloric acid is prepared by dissolving 36-38 wt% concentrated hydrochloric acid in deionized water at a volume ratio of 1:
3.
6. The porous carbon cathode material with high sulfur loading according to claim 3, characterized in that: In S1, the porous carbon includes a plurality of micropores with a pore size of 1.14±0.10 nm, a plurality of mesopores with a pore size range of 2.00-50.00 nm, and a plurality of macropores with a pore size range of 50.00-60.00 nm and above 100.00 nm, and the average pore size of the porous carbon is 2-20 nm, and the total pore volume is 0.1-5.0 cm 3 / g, BET specific surface area is 700~1200m 2 / g.
7. The porous carbon cathode material with high sulfur loading according to claim 1, characterized in that: The conductive agent is one or a combination of conductive carbon black, carbon nanotubes and acetylene black.
8. The porous carbon cathode material with high sulfur loading according to claim 1, characterized in that: The binder is one of sodium carboxymethyl cellulose, acrylonitrile multipolymer and polyvinylidene fluoride.
9. Use of a porous carbon cathode material with a high sulfur loading according to any one of claims 1 to 8 in a lithium-sulfur battery.
10. The use of a porous carbon cathode material with high sulfur loading according to claim 9, characterized in that: First, the porous carbon material with high sulfur loading is mixed with a dispersion medium, and the sulfur loading is 0.5-5.0 mg / cm 2 The positive electrode is coated on the surface of the aluminum current collector, and after coating, it is post-processed to obtain a positive electrode plate; the positive electrode plate is used as a working electrode, lithium metal is used as a counter electrode, and a diaphragm and an electrolyte are set to assemble a lithium-sulfur battery.
Citation Information
Patent Citations
High-capacity lithium-sulfur cathode material and preparation method and application thereof
CN111180681A
Spongy carbon material and preparation method and application thereof
CN108666569A